OVERVIEW OF BIOTERRORISM AND ITS AGENTS - REVATHY A.R; MENEZES GA (International Journal of Pharma and Bio Sciences, 2013)
Bioterrorism is the deliberate release of bacteria, toxins and viruses, or other microbes used to cause illness or death in people, animals, or plants. The Center for Disease Control and Prevention (CDC) has classified the biological agents into three categories based on the potential of use and risk factors as weapons. The biological agent should have the following characteristics in order to be effective for use in biological warfare: highly virulent, highly contagious, short incubation period, easy production, easy dispersion, easy handling, and susceptibility to target population. Usually found in nature, these agents are chemically changed to amplify their ability to cause disease, make them resistant to current medicines, or to increase their ability to be spread into the environment. These agents can be spread through the food, water or air. Since these biological agents are extremely difficult to detect, terrorists may use it. In this brief review we have reiterated the overview of bioterrorism and its agents.